PASAR JASA UMKM (USAHA MIKRO KECIL MENENGAH) BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract-- Many advances in information technology have changed the need for information more quickly. With the development of web based information it is expected that advances in technology can help solve the various problems that arise in fulfil the need for information . The system was developed using the PHP Hypertext Preprocessor ( PHP ) as the programming language , MySQL as the database , XAMPP and Web Browser . As a development tool used applications like Adobe Dreamweaver 3 . With this system , it will be easier for the user to view a variety of services MSMES in Semarang and users can add services that are owned through this website for free . Keywords : Market Services of MSMES, E - Commerce .